Translation as an indispensable weapon in the fight against HIV and AIDS in Lesotho. Issue 4 (2nd October 2018) - Sebotsa, Mosisili; Leshota, Lekholokoe
Abstract: HIV and the AIDS pandemic were introduced in the African continent as Western medical concepts that had no functional equivalence in the African cultures. It was in this context that African health authorities had to decrypt HIV/AIDS scientific processes in order to come up with a translation that captures the essence of these concepts and that decodes them in a manner that is understandable to the common man. In this regard, Lesotho was no exception. As a result, the government of Lesotho, the Ministry of Health, NGOs, health institutions and youth clubs undertook a mass-translation project to raise awareness among people of the same age group throughout the country. The present paper undertakes morpho-semantic and lexico-semantic analyses and employs the optic of hermeneutics of suspicion to explore or investigate the impact of translation on word coinage and the terminology used in the field of HIV/AIDS awareness and prevention. Translation's impact on the development of language at large, as well as the meanings that are implied in some of these neologisms are also explored.